RAPID ACOUSTIC PROCESSING IN THE AUDITORY BRAINSTEM IS NOT RELATED TO CORTICAL ASYMMETRY FOR THE SYLLABLE RATE OF SPEECH - Abrams, Daniel A. (2010)
OBJECTIVE: Temporal acuity in the auditory brainstem is correlated with left-dominant patterns of cortical asymmetry for processing rapid speech-sound stimuli. Here we investigate whether a similar relationship exists between brainstem processing of rapid speech components and cortical processing of syllable patterns in speech. METHODS: We measured brainstem and cortical evoked potentials in response to speech tokens in 23 children. We used established measures of auditory brainstem and cortical activity to examine functional relationships between these structures. RESULTS: We found no relationship between brainstem responses to fast acoustic elements of speech and right-dominant cortical processing of syllable patterns. CONCLUSIONS: Brainstem processing of rapid elements in speech is not functionally related to rightward cortical asymmetry associated with the processing of syllable-rate features in speech. Viewed together with previous evidence linking brainstem timing with leftward cortical asymmetry for faster acoustic features, findings support the existence of distinct mechanisms for encoding rapid vs. slow elements of speech. SIGNIFICANCE: Results provide a fundamental advance in our knowledge of the segregation of subcortical input associated with cortical asymmetries for acoustic rate processing in the human auditory system. Implications of these findings for auditory perception, reading ability and development are discussed.